15
2006-12-18 10:34:06
·
answer #1
·
answered by bad_sector 3
·
0⤊
0⤋
9+m
=9+6 for m=6
=15
2006-12-18 18:35:21
·
answer #2
·
answered by raj 7
·
0⤊
0⤋
15
2006-12-18 20:20:14
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
15
2006-12-18 18:46:13
·
answer #4
·
answered by RuN FaSt. WiN!! 2
·
0⤊
0⤋
15
2006-12-18 18:35:45
·
answer #5
·
answered by BarbieQ 6
·
0⤊
0⤋
You just replace the m in the problem with a 6.
so you end up with 9+6=15
2006-12-18 18:35:40
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
Substitute m = 6 into the equation
9 + 6 = 15
2006-12-18 18:34:57
·
answer #7
·
answered by novadeath69 2
·
0⤊
0⤋
Just plug in 6 for m...
9+6=15
2006-12-18 18:35:02
·
answer #8
·
answered by knock knock 3
·
0⤊
0⤋
Well, since m=6, and 9+6=14, the answer is 14.
2006-12-18 18:39:11
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋
thats a common sense answer. all you have to do is substitute m for 6 and do 9 + 6. duuuuuuuhhhhhhhhhhh.....9+6=15
2006-12-18 18:35:11
·
answer #10
·
answered by ♥Brittany♥ 6
·
0⤊
0⤋